shRNA desing based on natural and drug induced variability targeting conserved regions from HIV reverse transcriptase (2010)
Inhibition of HIV-1 by RNA interference can be achieved by the expression of short hairpin RNAs (shRNAs) targeting conserved sequences. We designed shRNAs against HIV-1 reverse transcriptase considering the variability of conserved regions within the retrovirus reverse transcriptase conserved domain cd01645, where the RNA dependent DNA polymerase activity of the enzyme resides. HXB2 (K03455) genome was used to choose regions with conserved residues important for enzyme activity. Regions were identified in multiple alignments from naive and drug-resistant isolates. A script was developed that predicted silencing efficiency based on previously reported parameters and that could identify highly frequent nucleotide combinations in a 21 base-long window within these regions. Higher number of sequence combinations was found in alignments from resistant isolates. shRNAs targeting reverse transcriptase active site residues W24 and P25 had scores over 7. Three-dimensional structural analyses from wild-type and resistant enzymes consistent with enormous variability explain the difficulties in finding a perfect region for RNAi mediated silencing. For clinical purposes, HIV-1 variability is an obstacle for efficient silencing from shRNAs designed towards a consensus sequence as there are too many functional variants of the enzyme. We suggest a complementary therapy using a combinatorial approach consisting of a mix of shRNAs targeting the most frequent viral variants from 1214 naïve genomes and 1381 from resistant variants, during a highly active antiretroviral therapy regimen.